2018
DOI: 10.1038/s41598-018-20422-0
|View full text |Cite|
|
Sign up to set email alerts
|

Omega-3 docosahexaenoic acid induces pyroptosis cell death in triple-negative breast cancer cells

Abstract: The implication of inflammation in pathophysiology of several type of cancers has been under intense investigation. Omega-3 fatty acids can modulate inflammation and present anticancer effects, promoting cancer cell death. Pyroptosis is an inflammation related cell death and so far, the function of docosahexaenoic acid (DHA) in pyroptosis cell death has not been described. This study investigated the role of DHA in triggering pyroptosis activation in breast cancer cells. MDA-MB-231 breast cancer cells were sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 66 publications
(75 reference statements)
3
113
1
2
Order By: Relevance
“…To date, many natural products from traditional Chinese medicines (TCMs) have been identified to have a potent anti-tumor effect [28,53]. TTM, a traditional Chinese medicine, was found to significantly suppress the proliferation of cancer cells and growth of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many natural products from traditional Chinese medicines (TCMs) have been identified to have a potent anti-tumor effect [28,53]. TTM, a traditional Chinese medicine, was found to significantly suppress the proliferation of cancer cells and growth of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasomes activation in response to a wide variety of endogenous or exogenous stimuli facilitates a programmed cell death, called pyroptosis via induction of caspase-1 activation. Therefore, inflammasomes have been reported to prevent cancer development and activation of inflammasomes was attributed to a mechanism for the anticancer agents, such as induction of pyroptosis by omega-3 docosahexaenoic acid in triple-negative breast cancer cells [27] and inhibition of hepatocellular carcinoma cell growth by estradiol [40]. However, in contrast to this notion, there has been an increasing appreciation that excessive inflammasomes activation could contribute to growth of the multiple types of cancer cells [18,19,22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of the inflammasome facilitates tumor progression [23,24], suggesting that inflammasomes act as mediators that bridge chronic inflammation and tumorigenesis. Interestingly, in contrast to this notion, it has been also well documented that the suppressive effects on tumor growth by various anticancer agents are mediated through inflammasomes activation, which initiates pyroptotic cell death in cancer cells [25][26][27]. These conflicting reports suggest that the outcome of inflammasomes activation in growth of cancer cells would be specific for cell type, tumor tissue, and the nature of the inducers or inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that MST1 interacts with ROS and plays critical roles in apoptosis, autophagy, and tumor suppression (39)(40)(41)(42). Recently, studies have also demonstrated that ROS induces pyroptosis and suppresses cancer progression (43,44). Thus, we first assess the levels of ROS on pyroptosis in PDAC cells.…”
Section: Mst1 Suppresses Proliferation Migration and Invasion Via Rmentioning
confidence: 99%